Pengaruh Program Pengembangan Sumber Daya Manusia terhadap Kualitas Audit Internal: Peran Mediasi Kompetensi Perilaku Auditor - Rudiana Fibriani; Gusti Dian Prayogi (MAPAN: Jurnal Manajemen Akuntansi Palapa Nusantara, 2025)
This study examines the relationship between human resource development (HR) programs and the quality of internal audits in manufacturing and service companies in Indonesia. With the increasing complexity of regulations and the demands of organizational accountability, the ability of internal auditors is no longer only determined by technical knowledge, but also by behavioral competence, emotional intelligence, and adaptability to technological changes. The study used a quantitative approach with a survey method of 143 internal auditors working in public companies and state-owned enterprises in Indonesia. The data was analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results of the study prove that technical competency training programs, cross-generational mentoring programs, and internal position rotation programs significantly affect audit quality. The study's unique finding is that cross-generational mentoring has the greatest influence on audit quality, surpassing the influence of conventional technical training. This research makes a new contribution to the internal audit literature by integrating human capital theory-based human capital theory-based human resource development perspectives into the audit quality framework.